Usage of Alternate Assessment Tool for Enhanced Understanding of Product Design and Development Course at BMSCE - Murthy, Madhav (Journal of Engineering Education Transformations, 2015)
Product Design and Development is a discipline that is required for engineers of all domains. In simple terms, product design brings in the users(human element) way of making a product. It is proved that, application of product design concepts paves way for successful product development with optimum utilization of resources. Product design is a set of tasks which starts with Product/Problem identification and followed by project planning, concept generation,selection, testing, prototyping, manufacturing the product to be produced. This course is a department elective for the students of seventh semester mechanical engineering. This article focuses on usage of alternate assessment tools for the enhanced understanding of the subject by the student. The students were made to design a questionnaire for the topics assigned to them in the class, which varied from 4 wheeler automobile to smart phone. The intention of using alternate assessment tool was multifold; i) Market exposure for the student ii)Implementation of theory into practice iii)Satisfaction of learning a course iv) Preparedness of using the course in their career.